Small band gap ferric pseudobrookite as a new photo-Fenton catalyst for degradation of phenolic acid - Ha Cam Anh; Nguyen Phung Anh; Nguyen Tri; Hoang Tien Cuong; Nguyen Thi Thuy Van; Luu Cam Loc (Journal of Science: Advanced Materials and Devices, 2022)
The influence of the calcination mode of sol–gel synthesis on the crystallization properties of ferric pseudobrookite Fe2TiO5 (FTO) was investigated. The characteristics of pseudobrookite were identified by various methods: TGA, XRD, FT-IR, BET adsorption, EDX, EDS mapping, Raman spectroscopy, UV-Vis, SEM, and TEM. The results indicate that ferric pseudobrookite crystals can be fabricated at a low calcination temperature of 600 °C and that crystallization can be controlled by the calcination regime. Calcination at 700 °C for 2 h creates the sample with the highest crystallinity and smallest crystal (31.3 nm) and particle size (20–35 nm). With its main components of ferric Fe2TiO5 and rutile TiO2, pseudobrookite can absorb visible light up to 653 nm and UV-A light with wavelengths shorter than 450 nm. The activity of the FTO obtained was estimated from the removal of phenolic acid in photocatalytic and photo-Fenton reactions under UV-A light irradiation using a batch method. The results show that Fe2TiO5 appears to be an excellent catalyst in a photo-Fenton process to decompose cinnamic acid (CA). The maximum CA conversion reached 96.2% after 280 min in a photo-Fenton process at pH 3.0, which is a much higher rate of conversion than in a photocatalytic reaction in air (20.0%). Further, Fe2TiO5 exhibits excellent stability in an acidic medium (pH = 3.0) and can easily be recovered and used repeatedly with stable performance. After ten batches of photo-Fenton reaction, CA conversion decreases by 10% and the catalyst structure is almost unchanged.